The Relationship between Visceral Fat and Percentage Fat with VO2max in Young Rowing Athletes - Fadhiil, Fahmi; Syafriani, Rini; Bahri, Samsul (Jurnal Pendidikan Jasmani (JPJ), 2024)
The author researched visceral fat factors, body fat percentage and young rowing athletes in West Bandung district with the aim of seeing the relationship between Visceral Fat and Body Fat Percentage on VO2max. Method: the subjects in this study were young rowing athletes in West Bandung Regency, the research used clinical trials that had approval from the Bandung Health Polytechnic Education Committee. The parameters measured include anthropometry involving visceral fat and body fat percentage and VO2max capacity. Results: The results show that the relationship between Visceral-Fat and VO2max results is (r = -0.499) with significant results (P = 0.118). This value can conclude that there is no relationship between Visceral-Fat and VO2max results in rowing athletes, while the correlation results show (r = -0.499) indicating that the correlation is inversely proportional to the degree of moderate correlation which can be concluded if the percentage value is greater Visceral-Fat then the resulting value of VO2max will be low.